Process engineering for pollution control and waste minimization - Wise, Donald L. (Donald Lee); Trantolo, Debra J. (Environmental science and pollution control series, 1994)
Offers up-to-date technical information on current and potential pollution control and waste minimization practices, providing industry-specific case studies, techniques and models.